2013
DOI: 10.1890/12-0833.1
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing litter size of marmots over time: a life history response to climate change?

Abstract: Abstract. The way that plants and animals respond to climate change varies widely among species, but the biological features underlying their actual response remains largely unknown. Here, from a 20-year monitoring study, we document a continuous decrease in litter size of the Alpine marmot (Marmota marmota) since 1990. To cope with harsh winters, Alpine marmots hibernate in burrows and their reproductive output should depend more on spring conditions compared to animals that are active year-round. However, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 29 publications
2
101
1
2
Order By: Relevance
“…Both of these closely related ( phylogenetically) populations are emerging from hibernation earlier in response to shifting environmental conditions, and as a result, are experiencing longer growing seasons [63][64][65]. Marmots in the Rocky Mountains have capitalized on this longer growing season with increased seasonal capital accrual that has resulted in larger litter sizes [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these closely related ( phylogenetically) populations are emerging from hibernation earlier in response to shifting environmental conditions, and as a result, are experiencing longer growing seasons [63][64][65]. Marmots in the Rocky Mountains have capitalized on this longer growing season with increased seasonal capital accrual that has resulted in larger litter sizes [64].…”
Section: Discussionmentioning
confidence: 99%
“…Marmots in the Rocky Mountains have capitalized on this longer growing season with increased seasonal capital accrual that has resulted in larger litter sizes [64]. In contrast, the positive effect of the longer growing season has been offset by higher capital storage costs associated with changing environmental conditions and a higher temperature-dependent metabolic rate in the French Alps marmot population, ultimately resulting in smaller litters there [65].…”
Section: Discussionmentioning
confidence: 99%
“…This is because increased energy intake during summer active months is strongly correlated with winter survival and reproduction (Kuhn and Vander Wall 2008). Recent studies of other marmot species have found a relationship between increased body mass gained over the active season and survival during hibernation, reproduction rates, and subsequent litter and population size (Ozgul et al 2010;Tafani et al 2012). However the efficacy of successful foraging is strongly associated with time invested otherwise in vigilance and other behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…A high snow depth ensures burrow insulation during hibernation, leading to larger litters [27] and favouring pup survival [28]. In turn, it results in more families with mature male subordinates 2 years later.…”
Section: Discussionmentioning
confidence: 99%
“…As observed for the yellowbellied marmots [16], we first expected winter conditions to have a relatively weaker influence on the annual proportion of EPLs than spring conditions. Second, we expected a strong positive effect from earlier springs on the annual proportion of EPLs because females and males could have more time to find mates, and their movements are easier in the absence of snow despite the better body condition of females when snow is abundant during winter [27]. As regards to indirect effects, we predicted snowy winters to indirectly increase the annual proportion of EPLs through its delayed effect on the social structure of the population.…”
Section: Introductionmentioning
confidence: 99%